PENGARUH MANAJEMEN LABA, RASIO KEUANGAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PERINGKAT OBLIGASI - Kiki Akbar Rizki; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Forum Manajemen STIMI Handayani Denpasar, 2018)
Bond rating is a transferable medium-term debt that contains a promisefrom the issuing party to pay the interest at a specified period and settle the debtprincipal at a predetermined time to the bond buyer. This study aims to re-examinethe influence of earnings management, financial ratios, and corporate governancemechanisms on bond ratings. The sample in this study are 10 financial and nonfinancial companies listed on Indonesia Stock Exchange for period 2013-2016.Research sample determination is using purposive sampling method. Research datawas analyzed by using logistic regression analysis. The results showed that earningsmanagement does not affect the bonds rating which shown with a significance value of 0.284. The financial ratios also has no effect on bond’s rating which is shown with a significance value of 0.856. And corporate governance also has no significanteffect on bonds rating with significance level of 0.885.